Home‐Based High‐Intensity Interval Training for People With Parkinson's: A Randomized, Controlled, Feasibility Trial - Conrad Harpham; Hilary Gunn; Jonathan Marsden; Raul Bescos‐Garcia; Christopher Murgatroyd; Luke Connolly (Health Science Reports)
ABSTRACT Background and Aims Home‐based high‐intensity interval training (HIIT) could be feasible and useful for people with Parkinson's (PwP). However, no home‐based HIIT program for PwP has been undertaken. This trial was designed to obtain preliminary data regarding the feasibility, acceptability and safety of HIIT‐Home4Parkinson's (HH4P), a previously co‐created home‐based HIIT program for PwP, explore outcomes that may be sensitive to change, and inform the implementation of a potential full trial. Methods A randomized, controlled feasibility trial was undertaken. Thirteen independently mobile PwP of Hoehn and Yahr stages 1–3 were randomized to the 12‐week, three times weekly HH4P HIIT program (n = 7), or usual care (n = 6). Feasibility and safety outcomes included aspects such as program completion, adherence, exercise intensity and adverse effects and events. Potential primary outcomes for a full trial were serum brain‐derived neurotrophic factor, maximal oxygen uptake and the Unified Parkinson's Disease Rating Scale part III. Process evaluation with a qualitative aspect explored implementation fidelity and participant thoughts and feelings. Results Six HIIT participants completed the program, with one withdrawing due to an unrelated back injury. Mean exercise adherence was 78.4%, while the mean exercise intensity was 77.2% HRmax per session, with three participants not achieving mean 75% HRmax. HIIT related adverse effects were minor and temporary, and the majority of exercise program and delivery procedures were deemed feasible and acceptable by participants. When compared to controls, the HIIT group did not experience benefits in any of the potential primary outcomes. Conclusion Preliminary data suggests that home‐based HIIT could be feasible, safe and acceptable for some PwP, although the capacity to stimulate the required exercise intensity, along with the potential benefits remain uncertain. Progression to a full HH4P trial cannot be recommended until further evaluation of aspects such as exercise type and model of support is undertaken. Trial Registration ClinicalTrials.gov NCT05485428.